From Reporting to Transformation: A Review of AI Tools Enabling Sustainability Governance Across Multi-Tier Supply Chains - Procházka, Petr; Velinov, Emil; Lacourbe, Paul (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This paper deals with the topic of artificial intelligence tools that have the capacity to assist with sustainability governance in multi-tier supply chains. These tools in the sustainability sector in general are meant to cut costs and enable small and medium enterprises and lower-tier suppliers to get access to best practices, streamline their sustainability efforts, and create universally comparable outputs. The added value of our research is to categorize existing tools, to identify potential gaps, and to enable users to understand the tools with the highest impact. We collect available solutions by a combination of desk research and interviews of industry experts from various levels of supply chain. We evaluate them by their capability to overcome five main challenges – data beyond simple reporting and manual collection, reach beyond Tier 1 suppliers, usability by small enterprises, involvement of artificial intelligence, and tools having an accessible cost. Having such an overview will assist low-key users with less resources to easily tap on existing solutions without large barriers.